Valorization of lignocellulosic rice husk producing biosilica and biofuels—a review. (1st January 2023) - Nawaz, Shahid; Jamil, Farrukh; Akhter, Parveen; Hussain, Murid; Jang, Hoyeon; Park, Young-Kwon
Abstract: Lignocellulosic biomass is an agricultural waste material abundantly produced in large quantities on earth. Rice husk (RH) is a type of lignocellulosic biomass and a huge byproduct of rice milling. Notably, the rice plant collects silica from the soil and stores the collected silica in the form of silicic acid inside the cellulose micro-compartments of the plant. Therefore, RH obtained from rice milling contains a significant quantity of amorphous silica, which can further be used for several other purposes. Furthermore, silica-rich RH can be employed as a raw material for the production of biofuels and biochars instantaneously via thermochemical processes such as pyrolysis and gasification. This article thoroughly explores a prospective method use to produce biosilica and energy from RH at the same time, which is currently under investigation. Moreover, this study also discusses current improvements in the synthesis of RH silica materials and their long-term use, particularly in energy and environmental functional materials. In terms of the environment, RH silica materials can remove heavy metals and organic pollutants in soil amendment, wastewater treatment, and gas purification via adsorption, catalysis, and integrative methods. In essence, there are numerous research and development obstacles to overcome in the production of biosilica and biofuels, respectively, from RH, and this review article highlights all of them.